The Influence of Human Resource Practices towards Improving Organizational Performance - Mansor, Mohd Fitri; Abu, Noor Hidayah; Kamil, Syahida; Nasir, Hussein (American-Eurasian Network for Scientific Information Journals (AENSI), 2014)
Background: Human Resource Management is one of pertinent function in organizations that facilitates the manpower to achieve both organizational and individual goals. Human Resources is the most valuable assets of any organization with the machines, materials and even the money, nothing get done without manpower. In view of that, the aim of study is to investigate the influence of human resource practices towards improving organizational performance. Objectives:The objectives of the study are to examine the relationship between training and development as well as compensation and benefits towards improving organizational performance. Again, the study also will identify the strongest variable that influence on improving organizational performance. Results: There are two positive hypotheses have been proposed to both variables which are training and development as well as compensation and benefits positively contributing improving organizational performance. Conclusion: The proposed framework is very important to the organization that acts as guidelines in preparing human resource strategy by human practioners particularly in deciding the decision on human resource outsourcing